Controlling Molecular Ordering in Aqueous Conducting Polymers Using Ionic Liquids. Issue 39 (8th August 2016) - Kee, Seyoung; Kim, Nara; Kim, Bong Seong; Park, Seongjin; Jang, Yun Hee; Lee, Seoung Ho; Kim, Jehan; Kim, Junghwan; Kwon, Sooncheol; Lee, Kwanghee
Abstract : The molecular ordering of aqueous conducting polymers is controlled using a rational method. By introducing various ionic liquids, which have designed electrostatic interactions to PEDOT:PSS solutions, the evolution of the molecular ordering of the PEDOT is manipulated. Consequently, highly ordered nanostructures are achieved with a reduced π–π stacking distance of ≈3.38 Å and, thus, a maximum σ dc of ≈2100 S cm –1 .